2022
DOI: 10.3390/cells11233732
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms to Target Cellular Senescence in Aging and Disease

Abstract: Cellular senescence is a state of irreversible cell cycle arrest in response to several stressors, including DNA damage, increased cellular oxidative stress, telomere shortening, oncogene activation, and a deep epigenetic remodeling [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Cellular senescence is characterized by high heterogenicity and the expression of complex phenotypes [ 2 , 7 ]. Many cellular and molecular signatures have been exploited as senescent markers, however, none of them are exclusively expressed in senescent cells [ 4 ]. In view of this, the combination usage of biomarkers emerges as an effective way to achieve specific and accurate recognition of senescent cells.…”
Section: Dual-targeting Fluorescent Sensors For Precisely Tracking Ce...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular senescence is characterized by high heterogenicity and the expression of complex phenotypes [ 2 , 7 ]. Many cellular and molecular signatures have been exploited as senescent markers, however, none of them are exclusively expressed in senescent cells [ 4 ]. In view of this, the combination usage of biomarkers emerges as an effective way to achieve specific and accurate recognition of senescent cells.…”
Section: Dual-targeting Fluorescent Sensors For Precisely Tracking Ce...mentioning
confidence: 99%
“…Cellular senescence, an irreversible state of cell cycle arrest, was firstly described in the 1960s by Hayflick and colleagues [ 1 , 2 ]. In addition to replicative senescence in which the shortening of telomeres is involved, senescence has been revealed to be related to various cellular stresses, such as DNA damage and reactive oxygen species (ROS), and thus is closely associated with a broad range of biological processes and diseases [ 3 , 4 , 5 ]. With increasing knowledge on the positive and negative aspects of cellular senescence, senescent cells have been recognized as attractive targets for antiaging approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Given that triggering cancer cell dormancy following conventional cancer therapies is almost inevitable, some authors have suggested a 'one-two punch' strategy in which the sequential treatment of cancer with pro-senescence therapy is followed by "senolytic" therapy [68,69]. Time will tell whether such an approach can be used to significantly improve the length and quality of life of cancer patients.…”
Section: Introductionmentioning
confidence: 99%